Forward and Reverse Signaling Mediated by Transmembrane Tumor Necrosis Factor-Alpha and TNF Receptor 2: Potential Roles in an Immunosuppressive Tumor Microenvironment - Qu, Yang; Zhao, Gang; Li, Hui (Frontiers in Immunology, 2017)
Tumor necrosis factor alpha (TNF-α) is a pleiotropic inflammatory cytokine produced mainly by activated macrophages, lymphocytes and other cell types. Two distinct forms of TNF-α have been identified, soluble TNF-α (sTNF-α) and transmembrane TNF-α (mTNF-α). Transmembrane TNF-α, the precursor of sTNF-α, can be cleaved by the TNF-α converting enzyme (TACE) and released as sTNF-α. sTNF-α binds primarily to TNF receptor 1 (TNFR1) and plays an important role in the inflammatory immune response, whereas mTNF-α interacts primarily with TNF receptor 2 (TNFR2) and mediates the promotion of cellular proliferation and survival and other biological effects. It has been reported that the interaction between mTNF-α and TNFR2 induces bi-directional signaling, forward and reverse signaling, in both mTNF-α and TNFR2 expressing cells. Increasing evidence shows that the forward and reverse signaling mediated by mTNF-α and TNFR2 might play a significant role in the tumor microenvironment. In this review, the role of the crosstalk between mTNF-α and TNFR2 in the tumor microenvironment will be discussed.